PENGARUH Mg TERHADAP KEKERASAN KOMPOSIT MATRIKS KERAMIK Al2O3/Al - Sahari, G.N. Anastasia; Zulfia, Anne; Siradj, Eddy S. (Makara Journal of Science, 2009)
Magnesium Effect to the Hardness of Al2O3/Al Ceramic Matrix Composites. Composite is an alternative material which has satisfying properties and can be accommodated for certain applications. Ceramic Matrix Composites (CMCs) is one of the composite types that are very interesting in terms of high temperature applications material. In this paper, we investigate the effects of Mg addition on the hardness of Al2O3 Ceramic Matrix Composites which was produced by directed metal oxidation (Dimox) method. The CMCs material is made by placing Al ingot under mixture alumina and percentage of Mg 5, 8, 10, and 12% wt. The processing temperature was 1100°C for 24 hours followed by cooling to room temperature in the furnace. The results show that increasing of infiltration, the hardness increased to 1221 VHN maximum at 8% wt Mg and then decrease again as the increment amount of Mg.